Disparities in Health Insurance Among Middle Eastern and North African American Children in the US - Florence J. Dallo; Kyrah K. Brown; Adebola Obembe; Tiffany Kindratt (SAGE Publishing, 2024)
Objective: To estimate and compare the proportion of foreign-born Middle Eastern/North African (MENA) children without health insurance, public, or private insurance to foreign- and US-born White and US-born MENA children. Methods: Using 2000 to 2018 National Health Interview Survey data (N = 311 961 children) and 2015 to 2019 American Community Survey data (n = 1 892 255 children), we ran multivariable logistic regression to test the association between region of birth among non-Hispanic White children (independent variable) and health insurance coverage types (dependent variables). Results: In the NHIS and ACS, foreign-born MENA children had higher odds of being uninsured (NHIS OR = 1.50, 95%CI = 1.10-2.05; ACS OR = 2.11, 95%CI = 1.88-2.37) compared to US-born White children. In the ACS, foreign-born MENA children had 2.11 times higher odds (95%CI = 1.83-2.45) of being uninsured compared to US-born MENA children. Conclusion: Our findings have implications for the health status of foreign-born MENA children, who are currently more likely to be uninsured. Strategies such as interventions to increase health insurance enrollment, updating enrollment forms to capture race, ethnicity, and nativity can aid in identifying and monitoring key disparities among MENA children.